Information Wars in Modern International Relations - Pakhota Nataliia V. (Bìznes Inform, 2022)
The article examines the concept of hybrid warfare as a major factor in shaping the system of modern international relations. Traditionally, this process took place in the military sphere: in the past, the most famous systems of international relations were created as a result of large-scale wars. Today, the main tool for achieving supremacy on the world stage are hybrid wars, the main danger of which is the lack of laws, principles and rules for hostilities. Hybrid wars are dangerous both for a particular region (leading to the loss of cultural and civilizational identity) and for the system of international relations in general (serving as a source of global instability and becoming more frequent). Such a war theoretically allows the attackers to maintain the conflict for a long hour: their financial costs and human losses will be incomparably less than in a normal war. The main features, examples and analytical model of hybrid warfare are considered. The difference between the concepts of hybrid warfare and hybrid threats as an element of the aggressor’s preparation for information warfare is considered. In the process of evolution, human society has become increasingly aware of the value, significance and effectiveness of information, not only as a tool for learning about the world and the basis for building communication, but also as an incredibly effective and powerful «weapon» that sometimes surpasses all known weapons. Current trends in global communication show that the flow of information is so diverse and contradictory that information is beginning to be both creative and destructive. Therefore, choosing relevant and important information is an important task for every Ukrainian. It is important to study and master media literacy, i. e., the the ability to find, navigate and critically evaluate information found in digital environments